Mieczysław Wallis w poszukiwaniu piękna - impresje z podróży - Zegzuła-Nowak, Joanna (Kultura-Społeczeństwo-Edukacja, 2015)
The article presents impressions from research expeditions of polish 19th century scholar - Mieczysław Wallis . This aesthetician, philosopher and historian of art was a great beauty lover. So, in his travels around the country and abroad he searched manifestations of the beauty in: architecture, painting, sculpture and formations of nature as well. His handwritten notes which contained his memories from these journeys are very important and intellectually atractive reading.